The Role of the Dulaim in the Coronation of King Faisal I - Mariam Faiq Ali Al Rawi; Jamal Hashem Dhuwaib (مجلة جامعة الأنبار للعلوم الإنسانية)
Aims: This study aimed to examine the political circumstances that led to the establishment of the monarchy in Iraq after World War I. It also aimed to investigate the role of local, regional, and international factors in the selection of Prince Faisal bin Hussein as the first king of Iraq. It also highlighted the impact of the 1920 Revolution on changing British policies and the significant role of the Dulaim tribes in granting legitimacy to the new monarchy. Methodology: The research adopted the analytical historical approach to study documents and references related to the period of British occupation (1918-1921) and analyzing the impact of the 1920 Revolution on British policies, the process of Faisal I's coronation, and the role of the tribes in it. Results: After analyzing all the data and the historical information, the results showed that after the British occupation of Iraq in 1917 and the imposition of the mandate, Britain faced widespread popular rejection, culminating in the 1920 Revolution, which forced the British government to change its policy. Therefore, Britain decided to establish a constitutional monarchy to secure its influence, so Prince Faisal I was chosen for his political experience and his role in the Great Arab Revolt. Tribal support was essential to Faisal's rule, and the Dulaim tribes played a pivotal role in pledging allegiance, which finally strengthened his legitimacy. Then, on August 23, 1921, Faisal I was proclaimed king, ushering in a new phase in the construction of the modern Iraqi state under the British influence. Conclusions: It can be concluded that the 1920 revolution forced Britain to seek an indirect system of rule. The selection of Faisal I was part of a British strategy to ensure control. Tribes, particularly those of the Dulaim, also played a key role in legitimizing the monarchy. However, Iraq remained under British influence until its full independence in 1958 .